MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MELALUI CTL - Shanti, Widha Nur; Sholihah, Dyahsih Alin; Abdullah, Ahmad Anis (Jurnal Pembelajaran Matematika, 2018)
Abstract: This study aims to explain how Contextual Teaching and Learning (CTL) approach adopted in the study of mathematics can develop student` critical thinking skills. The method used in this research is literature study (library research). The data in this study is a secondary data such as the results of the research as scientific books, scientific journals, research report, and other relevant sources. Data analysis techiques in the study include three stages, namely organize, synthesize, and identify. The research result showed that the Contextual Teaching and Learning (CTL) approach to the stages of learning, among others (1) presentation of problems/a real situation; (2) group discussion, which includes the finding activities and reflection; and (3) exercise a math problem, has relevance to the indicators on critical thinking skills, namely interpretation, analysis, evaluation, and decision. So that it can be concluded that Contextual Teaching and Learning (CTL) approach able to improve the critical thinking skills when applied in the study of mathematics.Keywords: CTL, Critical Thinking Skills